Pelatihan SIAPIK di Kelurahan Sumberrejo Kecamatan Balikpapan Tengah - Cipto, Rahajeng Cahyaning Putri; Hadiyatno, Didik; Susilowati, Dwi; Saraswati, Wiwik; Juwari, Juwari; Hendrawan, Yudhi; Moorcy, Nadi Hernadi; Novianti, Putri Ramadya; Firdaus, Muhammad Dzaky (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a very important role in increasing economic growth in Indonesia. The problem of MSMEs that often occurs is the recording of financial statements that have not been done properly. MSMEs consider recording financial statements difficult, complicated, and do not yet have the need for accounting applications. This service aims to help compile and record the financial statements of Bank Indonesia's fostered partners. One of the efforts made by Bank Indonesia is to encourage business capacity building and access to MSME financing by providing a means of recording financial statements. Bank Indonesia has created a web-based and mobile-based financial statement recording application called SIAPIK. SIAPIK is a digital-based financial recording application that is expected to make it easier for MSMEs to record their finances so that it can be a solution for MSME financial access to upgrade. The results of the survey on the quality of SIAPIK training can be concluded that the average assessment from participants of the implementation of the SIAPIK ToT is very good.